A moda da carne : relação entre homem e animal e o consumo de carne de marca - Oliveira Junior, Valdir Brito de (2016)
The aim of the present study was to understand if there is a carnism hegemony in current society and the relationship between consumers who are favorable and contrary to that specific diet. Firstly, it was performed a theoretical survey about the ethical and environmental consequences of meat production and consumption through a cultural point of view. Thereafter, taking into account the sociology of daily life, it was performed a research in some supermarkets aiming to demonstrate whether the aforementioned hegemony exists or not. Lastly, it was performed a netnography research in order to understand the risks and safety in branded meat consumption and the role of advertising in maintaining this habit.